Results of 14-year-long Enzyme Replacement Therapy in a Patient with Mucopolysaccharidosis Type II: Clinical Case - Natalia V. Zhurkova; Nato D. Vashakmadze; Ludmila K. Mikhaylova; Marina A. Babaykina; Nina V. Fedorova; Elena Yu. Voskoboeva; Ekaterina Yu. Zakharova; Leyla S. Namazova-Baranova (Вопросы современной педиатрии)
Background. Mucopolysaccharidosis type II (MPS II) is a rare hereditary disease from the group of lysosomal storage diseases, with progressive course. There is effective enzyme replacement therapy (ERT) for this disease, it prevents the development of severe complications and improves patients’ quality of life. Long-term follow-up of health changes in individuals on ERT is required for evaluating the treatment impact on disease progression and eventually on the quality of life of the patient and his family.Clinical case description. Results of 14-year-long follow-up of the patient with MPS II who was the first patient on ERT with idursulfase in Russia are presented. Improvement of growth, decrease in ENT-organs infections frequency, liver and spleen sizes decrease, general stabilization, no progression in cardiovascular and respiratory events, normal levels of glycosaminoglycans in urine are shown.Conclusion. Long-term therapy with idursulfase in severe MPS II stabilizes the patient’s somatic condition, prevents the development of severe complications in cardiovascular and respiratory systems, improves the quality of life of the patient and his family. Urinary glycosaminoglycans level decrease is the important indicator of the therapy efficacy along with overall patient's somatic state.